We Plow God's Fields The Life of James G.K. McClure - Ager, John Curtis (Appalachian State University, 1991)
This biography explores the life of James G. K. McClure, Jr., and his vision for a better life in the mountains of North Carolina. At his prompting, and under his leadership, The Farmers Federation was founded in Fairview, North Carolina, in 1920.